Financial Analysis of Mantis Shrimp (Lysiosquillina maculata Fabricus, 1793) Landed on Tanakeke Island - Nuraeni L Rapi; Fadillah Apliani (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
This study aims to analyze the financial aspects of mantis shrimp (Lysiosquillina maculata Fabricus, 1793) fishing conducted by local fishermen and landed on Tanakeke Island. Mantis shrimp is a marine species with high economic value but has not been optimally utilized. The research was conducted over a two-month period using a quantitative method and purposive sampling technique, involving surveys of thirty fishermen. Financial economic data were obtained through interviews and used to analyze costs, revenues, and profits. The results of the study show that economically, mantis shrimp fishing provides an average annual income of IDR 211,680,000, with a net profit of IDR 98,240,000, an R/C ratio of 2, and a payback period of three years. This study indicates that the community of Tanakeke Island can experience significant economic benefits from mantis shrimp fishing. However, the presence of shrimp being caught before reaching a viable catch size